2020
DOI: 10.1111/jcpp.13321
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural trajectories in youth at familial risk for schizophrenia or bipolar disorder according to development of psychosis spectrum symptoms

Abstract: Background: The evaluation of child and adolescent offspring of patients with schizophrenia (SzO) or bipolar disorder (BpO) may help understand changes taking place in the brain in individuals at heightened risk for disease during a key developmental period. Methods: One hundred twenty-eight individuals (33 SzO and 46 BpO, considered jointly as 'Familial High Risk' (FHR), and 49 controls) aged 6-17 years underwent clinical, cognitive and neuroimaging assessment at baseline, 2-and 4-year follow-up. Twenty FHR p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…A number of hypothetical neurodevelopmental models may explain the diverging gray matter trajectories in HR subjects depending on clinical outcome (Figure 2). For HR subjects that do not transition, gray matter volume may initially be lower than HV, but during adolescence non-transition subjects have a slower trajectory of typical gray matter loss, allowing typically developing subjects to "catch up" to the same level of gray matter volume, as shown in the NIMH cohort and the Barcelona cohort (21,52). This infers premature gray matter loss in HR or a neurodevelopmental deficit in gray matter volume, which no longer differs from HV later on in development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of hypothetical neurodevelopmental models may explain the diverging gray matter trajectories in HR subjects depending on clinical outcome (Figure 2). For HR subjects that do not transition, gray matter volume may initially be lower than HV, but during adolescence non-transition subjects have a slower trajectory of typical gray matter loss, allowing typically developing subjects to "catch up" to the same level of gray matter volume, as shown in the NIMH cohort and the Barcelona cohort (21,52). This infers premature gray matter loss in HR or a neurodevelopmental deficit in gray matter volume, which no longer differs from HV later on in development.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, remitted HR subjects may retain this deficit in gray matter volume, but to a lesser extent than that seen in subjects who transition to psychosis. The former is most likely, as studies generally do not find an intermediate level of gray matter loss in remitted subjects compared to HV and transitioned subjects (17,20,28,43,44,52). Cognition may be affected in HR subjects whose brain trajectories later "normalize, " as initial gray matter deficits alongside protracted loss are associated with poor intelligence (71), which is reported to be lower in GHR groups (72).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Convergent evidence has demonstrated widespread grey matter reductions in individuals with schizophrenia, including lower cortical volume (CV), reduced cortical thickness (CT) and smaller surface area (SA) and subcortical volumes, predominantly in the frontal and temporal regions 3,[15][16][17] . Longitudinal neuroimaging studies have demonstrated progressive grey matter changes related to schizophrenia [18][19][20] as well as morphological differences that may be present prior to the onset of symptoms 20,21 . High-risk familial studies have observed brain structural alterations in unaffected relatives of patients with schizophrenia relative to controls, suggesting a genetic contribution [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%